Pengantar Akuntansi: Mudah Membuat Jurnal dengan Pendekatan Siklus Transaksi/ Edisi IFRS - Samryn, L.M. (Rajawali, 2015)
Pengantar Akuntansi: Mudah Membuat Jurnal dengan Pendekatan Siklus Transaksi/ Edisi IFRS